Efficiency of riboflavin and ultraviolet light treatment against high levels of biofilm‐derived Staphylococcus epidermidis in buffy coat platelet concentrates. Issue 5 (5th April 2017) - Taha, M.; Culibrk, B.; Kalab, M.; Schubert, P.; Yi, Q.‐L.; Goodrich, R.; Ramirez‐Arcos, S.
Abstract : Background and Objectives: Staphylococcus epidermidis forms surface‐attached aggregates (biofilms) in platelet concentrates (PCs), which are linked to missed detection during PC screening. This study was aimed at evaluating the efficacy of riboflavin‐UV treatment to inactivate S. epidermidis biofilms in buffy coat (BC) PCs. Materials and Methods: Biofilm and non‐biofilm cells from S. epidermidis ST‐10002 and S. epidermidis AZ‐66 were individually inoculated into whole blood (WB) units (~10 6 colony‐forming units (CFU)/ml) ( N = 4–5). One spiked and three unspiked WB units were processed to produce a BC‐PC pool. Riboflavin was added to the pool which was then split into two bags: one for UV treatment and the second was untreated. Bacterial counts were determined before and after treatment. In vitro PC quality was assessed by flow cytometry and dynamic light scattering. Results: Bacterial counts were reduced during BC‐PC production from ~10 6 CFU/ml in WB to 10 3 –10 4 CFU/ml in PCs ( P < 0·0001). Riboflavin‐UV treatment resulted in significantly higher reduction of S. epidermidis AZ‐66 than strain ST‐10002 (≥3·5 log reduction and 2·6–2·8 log reduction, respectively, P < 0·0001). Remaining bacteria post‐treatment were able to proliferate in PCs. No differences in S. epidermidis inactivation were observed in PCs produced from WB inoculated with biofilm or non‐biofilm cells ( P > 0·05). Platelet activation was enhanced in PCs produced with WB inoculated with biofilms compared to non‐biofilm cells ( P < 0·05). Conclusion: Riboflavin‐UV treatment was similarly efficacious in PCs produced from WB inoculated with S. epidermidis biofilm or non‐biofilm cells. Levels of biofilm‐derived S. epidermidis ≥10 3 CFU/ml were not completely inactivated; however, further testing is necessary with lower (real‐life) bacterial levels.